PENGARUH PROFESIONALISME APARAT BIROKRASI TERHADAP KUALITAS PELAYANAN PUBLIK SATUAN POLISI PAMONG PRAJA DAN KEBAKARAN KABUPATEN MINAHASA SELATAN - TAWAANG, TASYA AGUITA; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2020)
Improving the quality of public services needed by Civil Servants and FreelanceWorkers not only in terms of quantity, but also requires the ability of professionalism that isdirectly proportional to the demands of the community. Human resource development in theranks of government (public organizations) needs to be directed at improving professionalskills accompanied by a spirit of service to the public (community). Professionalism ofbureaucracy and public services is becoming an increasingly strategic policy issue, because itis included as one of the factors that become criteria to achieve the smoothness of the goals ofan organization or agency. This uses quantitative descriptive methods and data collectiontechniques using questionnaires given forty respondents. The results of the validity andreliability tests show each question is valid and reliable. The results of this study indicate thatwhen the Civil Service Police Unit increases professionalism (height) will encourageimprovement quality of public services. .Keywords : Professionalism, Public Service Quality